Graphene Oxide Wrapped Amorphous Copper Vanadium Oxide with Enhanced Capacitive Behavior for High‐Rate and Long‐Life Lithium‐Ion Battery Anodes. Issue 12 (7th August 2015) - Zhao, Kangning; Liu, Fengning; Niu, Chaojiang; Xu, Wangwang; Dong, Yifan; Zhang, Lei; Xie, Shaomei; Yan, Mengyu; Wei, Qiulong; Zhao, Dongyuan; Mai, Liqiang
Abstract : Graphene oxide‐wrapped amorphous copper vanadium oxide is fabricated through a template‐engaged redox reaction followed by vacuum dehydration. This material exhibits high reversible capacity, excellent rate capability, and out standing high‐rate cyclability. The outstanding performance is attributed to the fast capacitive charge storage and the in situ formed copper with enhanced electrical conductivity.